Answer:
Step by Step Solution
More Icon
STEP
1
:
Equation at the end of step 1
STEP
2
:
3s2 - 2s + 1
Simplify ————————————
s2 - s + 2
Trying to factor by splitting the middle term
2.1 Factoring 3s2 - 2s + 1
The first term is, 3s2 its coefficient is 3 .
The middle term is, -2s its coefficient is -2 .
The last term, "the constant", is +1
Step-1 : Multiply the coefficient of the first term by the constant 3 • 1 = 3
Step-2 : Find two factors of 3 whose sum equals the coefficient of the middle term, which is -2 .
-3 + -1 = -4
-1 + -3 = -4
1 + 3 = 4
3 + 1 = 4
Observation : No two such factors can be found !!
Conclusion : Trinomial can not be factored